Safety and Stability Analysis of Demolition and Reconstruction of Existing Railway Bridge Piers and Caps - Pengxu Pan; Wei Chen; Pei Wu (Applied Sciences, 2023)
The process of bridge reconstruction often involves the demolition and reconstruction of bridge piers and caps, while most of the construction methods used in the previous bridge reconstruction projects changed the bridge-bearing positions. In this paper, an in situ replacement scheme of bridge piers and caps is proposed, which can maintain the existing stress state of the bridge without changing the bearing position. In order to figure out the safety and stability of the in situ replacement scheme of existing railway bridges, a steel support system model for the removal and reconstruction of the bridge piers and caps is established by ABAQUS, according to a domestic railway bridge reconstruction project, and verified by field measurement test. Based on the model, the stress and deformation of the steel support system under a trainload are analyzed, as well as those of the bearing foundation and the superstructure. The results show that the steel support system and steel pipe piles located directly below the line carrying the trainload are subjected to the greatest stress and deformation. While under various load conditions, the stress and deformation of the main components in the steel support system of the in situ replacement scheme meet the design requirements, and the structure is safe under a trainload. In addition, guided by the numerical calculation results, the implementation scheme, existing problems, and solutions of the project are introduced in detail, which can provide a reference for similar projects.